Green facile synthesis to develop nanoscale coordination polymers as lysosome-targetable luminescent bioprobes - Karim S.; Mukherjee S.; Mahapatra S.; Parveen R.; Das D. (My University, 2025)
Three new coordination polymers (CPs), namely [{M(HL)(L)(H2O)}(ClO4)(H2O)]8 (M = Zn for CP 1, Mn for CP 2, Cu for CP 3) were synthesized to explore their efficacy as lysosome-targetable luminescent bioprobes. The synthesized CPs were characterized by techniques including single-crystal X-ray analysis, FTIR spectroscopy and elemental analysis. Single-crystal analysis revealed the formation of iso-structural CPs displaying distorted adamantoid topology developed by bridging ligands and H-bonds connections and metals at the nodes. A green hand-grinding technique with a mortar and pestle resulted in nanoscale coordination polymers (NCPs) suitable for cell permeability and was further confirmed by SEM and DLS analyses. Two of these hand-ground nanoscale coordination polymers NCP 1 and NCP 2 showed excellent green luminescence and were explored as potential and selective long-time biotrackers towards lysosome using the human lung carcinoma cell line (A549). Strikingly, the developed bioprobe displayed excellent bio-availability, photostability and excellent selectivity towards lysosomes sustained by various in vitro cell imaging experiments. Moreover, the long-term probing ability of these NCPs turned out to be better than the commercially available lysosome tracker i.e. LysoTracker Red, indicating their potential real-life application in bio-imaging. To the best ofour knowledge, this is the first example of nonexpensive and less toxic essential transition metal-based nanoscale coordination polymers that can behave as effective lysosome-targetable luminescent bioprobes. © The Royal Society of Chemistry.